2017
DOI: 10.1164/rccm.201605-0946oc
|View full text |Cite
|
Sign up to set email alerts
|

A Missense Genetic Variant in LRRC16A/CARMIL1 Improves Acute Respiratory Distress Syndrome Survival by Attenuating Platelet Count Decline

Abstract: Rationale: Platelets are believed to contribute to acute respiratory distress syndrome (ARDS) pathogenesis through inflammatory coagulation pathways. We recently reported that leucine-rich repeat-containing 16A (LRRC16A) modulates baseline platelet counts to mediate ARDS risk.Objectives: To examine the role of LRRC16A in ARDS survival and its mediating effect through platelets.Methods: A total of 414 cases with ARDS from intensive care units (ICUs) were recruited who had exome-wide genotyping data, detailed pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…variables that are potentially linked, they concluded that LRRC16A variants are associated with ARDS risk and that a portion of the association is via influence of LRRC16A on platelet number (90,92). In a subsequent analysis, these investigators also found that the LRRC16A genotype influences the rate of decline in platelet number in patients with ARDS in the 28 days after ICU admission, as well as that an attenuated platelet count decline is associated with greater survival (89). Mediation analysis was again used to evaluate the relationship of decline in platelet number and the association of an apparent functional LRRC16A SNP with mortality.…”
Section: Platelets Have Complex Effects On Pulmonary and Systemic Endmentioning
confidence: 95%
See 2 more Smart Citations
“…variables that are potentially linked, they concluded that LRRC16A variants are associated with ARDS risk and that a portion of the association is via influence of LRRC16A on platelet number (90,92). In a subsequent analysis, these investigators also found that the LRRC16A genotype influences the rate of decline in platelet number in patients with ARDS in the 28 days after ICU admission, as well as that an attenuated platelet count decline is associated with greater survival (89). Mediation analysis was again used to evaluate the relationship of decline in platelet number and the association of an apparent functional LRRC16A SNP with mortality.…”
Section: Platelets Have Complex Effects On Pulmonary and Systemic Endmentioning
confidence: 95%
“…Platelet Numbers Are Altered in Critical Illness, Influence the Outcome of ARDS, and Are Regulated by Genetic Determinants in Clinical ALI Thrombocytopenia is common in critically ill patients at risk for, or with, ARDS and is associated with negative outcomes, including death (4,14,(85)(86)(87)(88)(89)(90). In clinical observations and a model of gram-negative pneumonia with sepsis, thrombocytopenia was associated with dysregulated inflammation and impaired host defense (76,91).…”
Section: Platelets Have Complex Effects On Pulmonary and Systemic Endmentioning
confidence: 99%
See 1 more Smart Citation
“…One SNP, studied in detail, causes a single–amino acid change in the LRR domain, decreased expression of mRNA, increased patient survival, and a decreased rate of platelet loss during the course of the illness (Wei et al , 2017). One potential scenario is that decreased CARMIL1 function impairs the actin cytoskeleton of the platelet, which lessens platelet activation and therefore mitigates the loss of circulating blood platelets.…”
Section: Roles Of Carmils At the Cellular And Organismal Levelsmentioning
confidence: 99%
“…Our previous study indicated that low platelet count was associated with increased ARDS risk [31] and poor survival [32]. Here, we observed that late-onset patients, who had significantly lower platelet count at the time of ARDS onset, had worse prognosis.…”
Section: Discussionmentioning
confidence: 54%